Hemoglobin SS Nigerian Woman First Diagnosed at the Age of 52 years with Manifestation Mimicking Tuberculosis of the Spine - Ugwu, Ngozi Immaculata (Niger Med J, 2020)
Sickle cell anemia (SCA) is an inherited disorder of hemoglobin due to the presence of abnormal hemoglobin in a homozygous state. Manifestation is usually in infancy or early childhood due to gradual decrease in hemoglobin F level as age advances. Diagnosis in middle age is unusual. We present a woman who was diagnosed of SCA for the first time at middle age. The aim was to bring to the knowledge of physicians that patients with SCA can also present late so high index of suspicion is required to make diagnosis. A 52-year-old woman presented to orthopedic clinic with complaints of generalized bone pain and low back pain. There was no history of trauma prior to the onset of the pain. There was no associated fever, weight loss, loss of appetite, nor weakness of the lower limbs. X-ray of the spine done showed wedge collapse of the 12(th) thoracic and first lumbar vertebrae with posterior angulation of the thoracolumbar junction giving dorsal kyphosis. Her mode of presentation raised a suspicion of tuberculosis of the spine to rule out multiple myeloma. However, investigations for tuberculosis and multiple myeloma were all negative. This necessitated the investigation for SCA and the diagnosis was confirmed. The diagnosis of SCA is usually made in infancy or early childhood. High index of suspicion is required to make the diagnosis at middle age.